Hasil Belajar PENINGKATAN HASIL BELAJAR DENGAN MENGGUNAKAN METODE ROLE PLAY MATERI MUNAKAHAT SISWA KELAS XII SMK NEGERI 2 PRABUMULIH: Metode Role Play - Lestarika, Lestarika; Abdurrahmansyah, Abdurrahmansyah; Firnawinda, Firnawinda (Guruku: Jurnal Pendidikan Profesi Guru, 2023)
The research aims to analyze the extent to which the role play learning method can improve the learning achievement of Class XII students at SMK Negeri 2 Prabumulih. The research methodology used is classroom action research carried out in 2 cycles. Regarding the research sample, there were 30 students in the Prabumulih XII Accounting class, 26 women and 4 men. The results of the search results obtained are: (1) Student academic achievement shows improvement from cycle to cycle. In cycle I, student activity showed a score of 74.7%, then in cycle II it increased to 84.1% and cycle III again increased to 92%, (2) Student responses to learning using demonstration and role playing methods, their impressions were very enjoyable , not saturated and easy to understand. (3) Improvement in student learning outcomes is expressed in the percentage of achievement. The percentage of points obtained in cycle I was 36.7% with the number of students completing as many as 11 students, in cycle II it increased to 80% with the number of students completing as many as 24 students, Based on the research results, it can be concluded that through the application of the role play learning method, role play can improve student learning outcomes. Based on the research results, it can be concluded that through the application of the role play learning method, student learning outcomes can be improved.